This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: g '( y ) = 1 y g ''( y ) =- 1 y 2 Extra Credit (1 pt) g ''( y ) does not exist when y = 0, but for every other y, g ''( y ) is negative. Therefore, the function g ( y ) is concave down for all y except y = 0, when there is no concavity (curvature). Find the derivative of the following function f ( x ) = 4 xe-x 2 f '( x ) = 4 ( x )( e-x 2 )(- 2 x ) + ( e-x 2 )(1) [ ] (This uses the chain rule learned in 2.9)...
View Full Document